Purification and conversion of Malaysian iron ores into industrial grade iron oxide colour pigment - Wong Y.W.; Woon H.S.; Tan C.Y. (Maney Publishing, 2023)
This work proposes a method of converting local iron ores into colour pigments to add commercial and technical values to the commodity. Iron ores were subjected to hammer-crushing and two milling techniques (low-energy ball milling and high-energy milling) to produce submicron or ultrafine pigment particles. Effects of different milling duration, speed and charge type on the particle size were investigated. X-ray diffraction and energy-dispersive X-ray spectroscopy scans revealed that the ores contain hematite and goethite phases, with 54% of Fe and 3538% of O. Particle size analysis showed that high-energy milling (14 hours, 11 mm charge, 550 rev min1) was effective in producing particles as small as 1379 m. Commision Internationale de l'Eclairage L?a?b?colour values measured were L?of 497, a?of 212 and b?of 158. © W. S. Maney &Son Ltd 2014.